1990
DOI: 10.1177/004051759006000904
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Cutaneous and Perceived Comfort Response to Fabric

Abstract: We studied stratum corneum water content, water evaporation from the skin surface, capillary blood flow, and skin temperature under three different garments worn by ten female subjects exercising and resting in a hot, humid environment (29.4°C, 75% RH). Single jersey knit fabrics made from 100% 1.5 denier polyester, 100% 3.5 denier polyester, or 100% cotton were made into long sleeve T-shirts and pants. Measures of stratum corneum water content using a microwave probe, evaporative water loss using an Evaporime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…1). In another study of the impact of initially dry fabrics on skin worn under hot humid conditions, Hatch (1990) (22) addressed this issue by blotting sweat from the skin surface before logging WVFD.…”
Section: Other Sources Of Variationmentioning
confidence: 99%
“…1). In another study of the impact of initially dry fabrics on skin worn under hot humid conditions, Hatch (1990) (22) addressed this issue by blotting sweat from the skin surface before logging WVFD.…”
Section: Other Sources Of Variationmentioning
confidence: 99%
“…Hatch et al 38 reported that the upper back skin hydration values among hijab coated with cotton, polyester 1.5 denier, and polyester 3.5 denier fibers were not significantly different in the dry state. In the wet state, the skin hydration values were significantly different, with cotton group having the lowest value and polyester 3.5 denier fibers having the highest.…”
Section: Discussionmentioning
confidence: 99%
“…In the wet state, the skin hydration values were significantly different, with cotton group having the lowest value and polyester 3.5 denier fibers having the highest. 38 The effects of hijab material, the number of garment layers, and the use of inner hijab toward the results of this study were adjusted by ensuring that the subjects’ scalp were in dry state for three hours prior to the biophysical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Thermophysiological clothing comfort depends on the heat and moisture transport properties of the garment that provide the body's heat balance [8][9]. In the literature, parameters affecting thermophysiological comfort are given as personal features, environmental features and clothing features [10][11][12][13][14][15][16][17]. Major clothing properties affecting thermal comfort include thermal conductivity, water vapor permeability, air permeability and water impermeability [2].…”
Section: Introductionmentioning
confidence: 99%